Bone Protective Effects of Danggui Buxue Tang Alone and in Combination With Tamoxifen or Raloxifene in vivo and in vitro - Zhou, Li-Ping; Wong, Ka-Ying; Yeung, Hoi-Ting; Dong, Xiao-Li; Xiao, Hui-Hui; Gong, Amy G.-W.; Tsim, Karl W.-K.; Wong, Man-Sau (Frontiers in Pharmacology, 2018)
Danggui Buxue Tang (DBT), a traditional Chinese Medicine decoction containing Astragali Radix (AR) and Angelicae Sinensis Radix (ASR), is commonly prescribed for women in China as a remedy for menopausal symptoms. Previous study indicated that DBT stimulated cell growth and differentiation of human osteosarcoma MG-63 cells and exhibited estrogenic properties via estrogen receptors (ERs). The present study aimed to study the bone protective effects of DBT and its potential interactions with Selective Estrogen Receptor Modulators (SERMs, tamoxifen and raloxifene) in both in vivo and in vitro models as they act via similar ERs. Six month-old Sprague Dawley rats were randomly assigned to the following treatments for 12 weeks: 1) sham-operated control group with vehicle (sham), 2) ovariectomized group with vehicle (OVX), 3) OVX with 17ß-estradiol (E2, 2.0mg/kg.day), 4) OVX with tamoxifen (Tamo, 1.0mg/kg.day), 5) OVX with Raloxifene (Ralo, 3.0mg/kg.day), 6) OVX with DBT (DBT, 3.0g/kg.day), 7) OVX with DBT+Tamoxifen (DBT+Tamo) and 8) OVX with DBT+Raloxifene (DBT+Ralo). Effects of DBT and potential interactions between DBT and SERMs were also evaluated in MG-63 cells. DBT, tamoxifen, raloxifene and their combinations significantly increased bone mineral density (BMD) and improved trabecular bone properties, including bone surface (BS), trabecular bone number (Tb.N) and trabecular bone separation (Tb.Sp), as well as restored changes in bone turnover biomarkers and mRNA expression of genes involved in bone metabolism in OVX rats. Furthermore, DBT, SERMs and their combinations significantly increased serum estradiol and suppressed follicle stimulating hormone (FSH) and luteinizing hormone (LH) in OVX rats, suggesting the possible involvement of the hypothalamus-pituitary-gonadal axis in mediating their bone protective effects. However, SERMs, but not DBT, significantly increased uterus index in OVX rats. DBT significantly induced ALP activity and estrogen response element-dependent transcription in MG-63 cells. Our study demonstrated that DBT alone and in combinations with SERMs could exert bone protective effects in vitro and in vivo.